Regular Moderate or Intense Exercise Prevents Depression-Like Behavior without Change of Hippocampal Tryptophan Content in Chronically Tryptophan-Deficient and Stressed Mice - Lee, Hosung (Public Library of Science, 2013)
Regular exercise has an antidepressant effect in human subjects. Studies using animals have suggested that the antidepressant effect of exercise is attributable to an increase of brain 5-hydroxytryptamine (5-HT); however, the precise mechanism underlying the antidepressant action via exercise is unclear. In contrast, the effect of 5-HT on antidepressant activity has not been clarified, in part because the therapeutic response to antidepressant drugs has a time lag in spite of the rapid increase of brain 5-HT upon administration of these drugs. This study was designed to investigate the contribution of brain 5-HT to the antidepressant effect of exercise. Mice were fed a tryptophan-deficient diet and stressed using chronic unpredictable stress (CUS) for 4 weeks with or without the performance of either moderate or intense exercise on a treadmill 3 days per week. The findings demonstrated that the onset of depression-like behavior is attributable not to chronic reduction of 5-HT but to chronic stress. Regular exercise, whether moderate or intense, prevents depression-like behavior with an improvement of adult hippocampal cell proliferation and survival and without the recovery of 5-HT. Concomitantly, the mice that exercised showed increased hippocampal noradrenaline. Regular exercise prevents the impairment of not long-term memory but short-term memory in a 5-HT-reduced state. Together, these findings suggest that: (1) chronic reduction of brain 5-HT may not contribute to the onset of depression-like behavior; (2) regular exercise, whether moderate or intense, prevents the onset of chronic stress-induced depression-like behavior independent of brain 5-HT and dependent on brain adrenaline; and (3) regular exercise prevents chronic tryptophan reduction-induced impairment of not long-term but short-term memory.